Selective cauterization of supporting ligaments at Non Descent Vaginal Hysterectomy (NDVH) - M., Jayaraman Nambiar; Pai, Muralidhar V.; Poojary, Vidyashree; Upadhay, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to study the use of electrocautery selectively for cardinal uterosacral ligament complex during NDVH. Methods: We performed a series of NDVH where electrocautery was used selectively for the uterosacral cardinal ligament complex. Rest all stumps were clamped, divided and ligated. Results: We did a series of 21 cases using this technique and found this as a very effective method of doing NDVH. There were no major complications. Conclusion: Selective use of electrocautery for uterosacral and cardinal ligament complex makes NDVH easy.